Long-term follow-up in pediatric intensive care-a narrative review - Ashfaque Quadir; Ashfaque Quadir; Marino Festa; Michelle Gilchrist; Kate Thompson; Natalie Pride; Natalie Pride; Shreerupa Basu; Shreerupa Basu (Frontiers Media S.A., 2024)
Pediatric intensive care is a rapidly developing medical specialty and with evolving understanding of pediatric pathophysiology and advances in technology, most children in the developed world are now surviving to intensive care and hospital discharge. As mortality rates for children with critical illness continue to improve, increasing PICU survivorship is resulting in significant long-term consequences of intensive care in these vulnerable patients. Although impairments in physical, psychosocial and cognitive function are well documented in the literature and the importance of establishing follow-up programs is acknowledged, no standardized or evidence-based approach to long-term follow-up in the PICU exists. This narrative review explores pediatric post-intensive care syndrome and summarizes the multifactorial deficits and morbidity that can occur in these patients following recovery from critical illness and subsequent discharge from hospital. Current practices around long-term follow-up are explored with discussion focusing on gaps in research and understanding with suggested ways forward and future directions.